2018
DOI: 10.3906/bot-1711-46
|View full text |Cite
|
Sign up to set email alerts
|

The epilithic and epipelic diatom flora of the Balikhli River, Northwest Iran

Abstract: The Balikhli Chay is a permanent river in Ardabil Province, Iran. It originates from the Bozgoosh and Sabalan elevations in Northwest Iran. The water catchment area of the Balikhli River (Balikhli Chay) is over 1600 km 2 . Twenty-five kilometers to the southwest of the city of Ardabil, the Yamchi dam has been constructed on the river. The Yamchi reservoir serves as the main source for drinking and irrigation purposes. Several important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Seasonal changes in various forms such as the effect on air temperature, river inflows and consequently increase nutrients, water flows and consequently salinity changes in river inflows and decrease salinity can have important effects on the population change of diatoms [19]. In this study, Cyclotella mnengiana was observed in all sampling periods and so Cyclotella mnengiana often found in oligotrophic environments, both marine and fresh water ecosystems.…”
Section: Wwwblogspotcommentioning
confidence: 54%
“…Seasonal changes in various forms such as the effect on air temperature, river inflows and consequently increase nutrients, water flows and consequently salinity changes in river inflows and decrease salinity can have important effects on the population change of diatoms [19]. In this study, Cyclotella mnengiana was observed in all sampling periods and so Cyclotella mnengiana often found in oligotrophic environments, both marine and fresh water ecosystems.…”
Section: Wwwblogspotcommentioning
confidence: 54%
“…Based on the comparison study the Cymbella pernodensis Maillard, has not been reported in Iran [19][20][21][22][23][24][25][26][27][28][29][30]. It is a freshwater taxon which occurred only in stations 5 & 6, in all months except spring with the following environmental conditions: alkaline pH (8.71), moderate to high conductivity (502-834 μs.cm -1 ), oligotrophic to eutrophic conditions, temperature (4.9 -19.9 °C), TDS (164 -335 mg.l -1 ), BOD (˂ 8 mg.l -1 ), DO (˂ 10 mg.l -1 ), ORP (102), Salinity (< 0.…”
Section: Oceanography and Fisheries Open Access Journalmentioning
confidence: 99%
“…The physicochemical parameters presented the pH range of 6.7-6.9 for the Tizab spring that was neutral and the pH of 7.5-7.7 for the Tizab River which was slightly alkaline. Therefore, (Jamaloo et al, 2006;Moghadam, 1975;Witkowski et al, 2007;Compere, 1981;Kheiri et al, 2018a;Wasylik, 1975 (Moghadam, 1975;Soltanpour-Gargari et al, 2011;Atazadeh et al, 2007;Synder et al, 2001;Witkowski et al, 2007;Nejadsattari, 2005;Compere, 1981;Panahy-Mirzahasanlou et al, 2018;Kheiri et al, 2018a; (Moghadam, 1975;Wasylik, 1975;Soltanpour-Gargari et al, 2011;Compere, 1981;Nejadsattari, 2005; (Moghadam, 1975;Soltanpour-Gargari et al, 2011;Atazadeh et al, 2007;Witkowskiet al, 2007;Shams et al, 2012;Nejadsattari, 2005;Cheraghpour et al, 2013;Zarei-Darki, 2009a;Compere, 1981;Panahy-Mirzahasanlou et al, 2018;Shariatmadari et al, 2007; (Moghadam, 1975;Synder et al, 2001;Witkowski et al, 2007;Zarei-Darki, 2011a;Kheiri et al, 2018a;Kheiri et al, 2018b;Hirano, 1973;.…”
Section: Location and Description Of The Sampled Spring And The Sprinmentioning
confidence: 99%
“…4 Ref : Hofmann et al, 2011 (p. 315, pl. 97:15-20) Dimension: 16.20 μm long, 3.80 μm wide, 2005;Zarei-Darki, 2011a;Compere, 1981;Panahy-Mirzahasanlou et al, 2018;Kheiri et al, 2018b). (Noroozi et al, 2008).…”
Section: Distribution In Iran: This Taxon Is Widespreadmentioning
confidence: 99%
See 1 more Smart Citation